2017
DOI: 10.1002/jsfa.8458
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analyses to evaluate the effect of drought stress on selected African Eggplant accessions

Abstract: BACKGROUND: Drought stress is one of the main abiotic stresses that affect crops. It leads to biochemical changes that can have adverse effects on plant growth, development and productivity. African eggplants are important vegetable and fruit crops reported to adapt and thrive well under drought stress. The diversified metabolites arising due to stress have not been well defined. A gas chromatographic-mass spectrometric metabolomic approach was applied to characterize the effect of drought stress on metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…Apart from proline, several other amino acids were clearly induced in YN211 but not in HX10. Many amino acids have been shown in response to the water/drought stress either at a higher or lower level [45,46]. Proline is one of the main osmolytes in plants and could accumulate in response to various abiotic stresses [47].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from proline, several other amino acids were clearly induced in YN211 but not in HX10. Many amino acids have been shown in response to the water/drought stress either at a higher or lower level [45,46]. Proline is one of the main osmolytes in plants and could accumulate in response to various abiotic stresses [47].…”
Section: Discussionmentioning
confidence: 99%
“…The TCA- cycle regulates the synthesis of several amino acids [83]. Higher amount of glutamic acid, GABA and threonine was found in Soissons, Žitarka, Toborzó and Antonija under drought as compared to Srpanjka and Ellvis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, proline has been reported to be the most abundant osmolyte accumulated in response to multiple environmental stresses including water stress and pathogen infection, which acts as an ROS scavenger as well ( De Ronde et al, 2000 ; Hanci and Cebeci, 2014 ; Rodziewicz et al, 2014 ). Recent findings have demonstrated that water stressed eggplants accumulated osmoprotectants like proline, as well as glucose and fructose and this phenomenon has been correlated with increased tolerance toward water deficit and prevention from wilting ( Mibei et al, 2018 ). Our results showed significant difference between control plants and water stressed or V. dahliae infected plants in proline concentration, however, no significant difference was observed between control plants and plants under combined stress for the Skoutari cultivar.…”
Section: Discussionmentioning
confidence: 99%